Speaking Anxiety of Students of Parit Baru English Village - Laurensius Tingang; Aunurrahman Aunurrahman; Ageung Darajat (IKIP PGRI Pontianak, 2022)
This Research aims to find out the kinds and sources of speaking anxiety of the Students of English Parit Baru Village, Sungai Raya Regency in the academic year of 2021. This research used the descriptive qualitative method. Ten students from different grades of primary school around Parit Baru village were involved in this research. This research used a semi-structured interview and field note as the tool of collection data. data collection used an observation about students’ behavior during class that direct students to become Anxiety. The result showed that the kinds of speaking anxiety of English Parit Baru Village students were trait anxiety, where several students keep silent when the tutor ask them, students incapable to express their feelings, ideas, and thought; situation-specific anxiety when the tutor ask students to speak they sometimes can do it, in other condition or topics they also incapable to speak; state anxiety, when students ask by their tutor to speak suddenly, they cannot control their nervousness. Furthermore, the sources of speaking anxiety from personal anxiety can be overcome by actively of students during learning; interpersonal anxiety students need any motivation to learn speaking skills; teacher belief about language learning can be manifest by a good impression of teacher during teaching. For classroom procedure, the class needs to be relaxed; language testing derived from fear, shame, and doubt of the students.